2017
DOI: 10.3389/fimmu.2017.00913
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Plasma Cell Differentiation Defects in B Cell Expansion with NF-κB and T Cell Anergy Patient B Cells

Abstract: B cell Expansion with NF-κB and T cell Anergy (BENTA) disease is a novel B cell lymphoproliferative disorder caused by germline, gain-of-function mutations in the lymphocyte scaffolding protein CARD11, which drives constitutive NF-κB signaling. Despite dramatic polyclonal expansion of naive and immature B cells, BENTA patients also present with signs of primary immunodeficiency, including markedly reduced percentages of class-switched/memory B cells and poor humoral responses to certain vaccines. Using purifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…Low serum IgM and IgA levels are noted in some patients, with IgG being variable. In vitro studies of naïve patient B cells demonstrated impaired B cell differentiation into plasmablasts and long-lived plasma cells, consistent with poor IgG secretion in culture ( 106 ). These defects could be explained in part by a failed induction of specific factors required for plasma cell commitment, including BLIMP-1 and XBP-1.…”
Section: Card11mentioning
confidence: 98%
“…Low serum IgM and IgA levels are noted in some patients, with IgG being variable. In vitro studies of naïve patient B cells demonstrated impaired B cell differentiation into plasmablasts and long-lived plasma cells, consistent with poor IgG secretion in culture ( 106 ). These defects could be explained in part by a failed induction of specific factors required for plasma cell commitment, including BLIMP-1 and XBP-1.…”
Section: Card11mentioning
confidence: 98%
“…Thus, both cRel and RelA are indispensable for humoral immunity but for different functional reasons. However, a recent study showed that in the genetic disease B cell expansion with NFkB and T cell anergy (BENTA), constitutively active NFkB results in reduced ASC generation (Arjunaraja et al, 2017), suggesting that precise regulation of each NFkB dimer is required for healthy ASC generation.…”
Section: Introductionmentioning
confidence: 99%
“…Poor humoral immune responses in these patients are also reflected in very low frequencies of circulating class-switched and memory B cells, as well as low levels of IgM and IgA in the serum. Impaired humoral immunity in BENTA is evidenced by intrinsic defects in plasma cell differentiation and antibody secretion upon stimulation of naïve patient B cells in vitro , despite normal proliferation and enhanced survival ( 41 ). The hyporesponsiveness of BENTA patient T cells to in vitro stimulation, including poor proliferation and reduced IL-2 secretion, may also contribute to defective class-switched Ab responses ( 23 , 35 ).…”
Section: Benta Diseasementioning
confidence: 99%
“…The authors connected some of these defects to enhanced expression of the transcriptional repressor Blimp-1, which has been shown to promote T cell exhaustion. Although we have not measured Blimp-1 in BENTA T cells, we recently characterized a profound, intrinsic defect in patient B cell differentiation linked to failed induction of Blimp-1 ( 41 ). Clearly much more work is required to understand how elevated NF-κB activation perturbs seemingly independent pathways downstream of TCR signaling.…”
Section: Mechanisms Underlying Benta Susceptibility To Ebvmentioning
confidence: 99%